2020
DOI: 10.1080/17434440.2021.1860018
|View full text |Cite
|
Sign up to set email alerts
|

EEG modulation by different transcranial direct current stimulation (tDCS) montages: a randomized double-blind sham-control mechanistic pilot trial in healthy participants

Abstract: Background: Based on our Phantom study on transcranial direct current stimulation (tDCS), we hypothesized that EEG band power and field confinement would be greater following left dorsolateral prefrontal cortex (DLPFC -F3) tDCS using circular vs. rectangular electrodes. Methods: Double-blind randomized trial comparing tDCS with anode over the left DLPFC (groups: rectangular electrodes, circular electrodes, sham) and 2 active subgroup references (right shoulder vs. right DLPFC cathodes). Results: Twenty-four ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Compared with the sham group, real tDCS significantly increased electrical activity in the left dorsolateral prefrontal and the entire brain cortex, particularly high-frequency electrical activity, i.e., alpha and beta. Similar results were also obtained in previous studies, for example, tDCS to left DLPFC improved alpha power of the prefrontal cortex in patients with a minimally conscious state ( Cavinato et al, 2019 ), and beta PSD of left DLPFC ( El-Hagrassy et al, 2021 ). Although it remains unclear for many oscillatory frequencies whether their activity reflects the engagement or disengagement of sustained attention ( Kamiński et al, 2012 ; Clayton et al, 2015 ), some studies still reflected positive results of oscillatory EEG features and cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the sham group, real tDCS significantly increased electrical activity in the left dorsolateral prefrontal and the entire brain cortex, particularly high-frequency electrical activity, i.e., alpha and beta. Similar results were also obtained in previous studies, for example, tDCS to left DLPFC improved alpha power of the prefrontal cortex in patients with a minimally conscious state ( Cavinato et al, 2019 ), and beta PSD of left DLPFC ( El-Hagrassy et al, 2021 ). Although it remains unclear for many oscillatory frequencies whether their activity reflects the engagement or disengagement of sustained attention ( Kamiński et al, 2012 ; Clayton et al, 2015 ), some studies still reflected positive results of oscillatory EEG features and cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…The left frontal region included electrodes Fp1, F3, and F7; the right frontal region included electrodes Fp2, F4, and F8; the central region included electrodes Cz, C3, and C4; and the parieto-occipital region included electrodes Pz, P3, P4, O1, and O2. Absolute power spectrum density value (μV 2 /Hz) ( Thatcher et al, 2005 ; El-Hagrassy et al, 2021 ) in each frequency band (delta: 0.1–4 Hz; theta1: 6–8 Hz; theta2: 8–10 Hz; alpha1: 8–10 Hz; alpha2: 10–13 Hz; beta: 13–30 Hz) ( Tarasova et al, 2019 ) were computed using fast Fourier transform with the Welch method ( Welch, 1967 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are also many tDCS intervention target options for DOC patients. tDCS can be applied over the left DLPFC, posterior parietal cortex, and left primary sensorimotor cortex [ 6 , 16 , 17 ]. In clinical studies, these above tDCS stimulation targets have been reported to have intervention effects on DOC patients.…”
Section: Introductionmentioning
confidence: 99%